The Essayistic Form in Antonio Candido's Literary Criticism: Tradition and Rupture - Andrade, Rangel Gomes [UNESP]; Vicente, Adalberto Luis [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2020)
Antonio Candido is one of the most important Brazilian essayists. While exploiting the essayistic form, Candido joins an important tradition, which has marked national thinking. However, the critic gives a step forward in terms of tradition as he combines it with a solid theoretical knowledge from his academic education, promoting a level of specialization his predecessors had lacked. Basing on essay theorists, interpreters of Candido's work, and having the critic Sergio Milliet as the transition point between Candido's previous and current generation, we intend to promote reflection on Candido's essayistic style departing from a movement that aims to situate him on the limits of tradition and rupture.
Keywords: Antonio Candido; essay; literary criticism.